PEMBINAAN PEDAGANG MAKANAN KAKI LIMA UNTUK MENINGKATKAN HIGIENE DAN SANITASI PENGOLAHAN DAN PENYEDIAAN MAKANAN DI DESA PENATIH, DENPASAR TIMUR - I Nengah Sujaya; Ni Made Utami Dwipayanti; Ni Ketut Sutiari; L.P Lila Wulandari; Ni Kadek Tresna Adhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
Abstract Generally street vendor has little knowledge on hygiene and sanitation of food handling. Usually they trade in a night market or on street sides. There are two markets in Penatih Village that operate night market. Both markets located in a strategic location thus they have many visitors every day. In these two markets there are some vendors that need to be counseled and assisted in order to improve their knowledge on hygiene and sanitation of food handling. The counseling and assistance was conducted every week from 25 September to 10 October 2009, with 10 vendors as target participants. The venues were located in Penatih Market and Agung Market, Penatih Village, East Denpasar. The activities were conducted in the form of counseling and assisting during trading hours towards the participants in regards of hygiene and sanitation of food handling. In order to evaluate and measure the knowledge improvement of the participants, pre test and post test were carried out. The result shows that, most of participants have less knowledge on food additives in terms of usage, types and risk of usage. The participants have good knowledge on usage of clean water for utensil and food washing as well as knowledge on personal hygiene. It is recommended to conduct a continuous and regular counseling to street vendors with the involvement of local primary health care (puskesmas).